How Do Foreign Aid Agencies Learn? A Comparative Analysis of Organisational Learning Determinants in National Donor Bureaucracies - Heiner Janus; Daniel E. Esser (The European Journal of Development Research, 2025)
We distil and validate a new theory of organisational learning (OL) to understand OL in foreign aid agencies. Reviewing existing scholarship on OL in the public sector, we devise a theorectical framework consisting of three variables that connect interacting dimensions co-determining the organisation-specific intensity of OL: (1) individual knowledge acquisition, (2) social practices and (3) organisational political embeddedness. To validate our approach to studying OL empirically, we heed calls for more comparative research on OL by analysing 89 randomly sampled interviews with national development bureaucrats in Germany, South Korea and Norway. Our analysis demonstrates that our theoretical framework explains varying intensities of OL across the three cases. Crucially, it reveals the second dimension, social practices, to be decisive. While all cases in our sample contain evidence of individual learning and awareness of the organisations' context-specific political embeddedness, we observe distinct social practices in each organisation. The organisation in which OL is most vibrant is the only one in our sample social practices that are directly conducive to OL. These practices comprise unsanctioned negotiations of organisational objectives among staff, as well as a consensus to prioritise evidence and terminate failed projects, despite political pressures to spend more, faster. We conclude that future research on OL needs to eschew references to hypothetical best practices and instead study OL empirically and comparatively by connecting previously disjointed scholarly literatures through theory.
Keywords: 330; Bureaucrats; Development bureaucracy; Foreign aid; Organisational learning; Randomised interviews; Social practices